2022
DOI: 10.30574/wjbphs.2022.9.2.0037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on the effect of selected oral contraceptives on the liver functionality and integrity

Abstract: Oral contraceptives have been useful in birth control and other gynecological disorders; it is sometimes abused due to ignorance and other underlying factors. The liver is saddled with the responsibility of drug metabolism. This study assessed the effect of oral contraceptives on the liver functionality and integrity. A total of 25 female albino rats were obtained and allowed to acclimatize in the animal house of the department of Pharmacology, Rivers State University for 7 days. The rats were divided into fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…The mean serum levels of AST, ALT and ALP in the current study were 47.07 (± 14.79), 35.83 (± 13.78) and 63.34 (±14.74) respectively; the result concur with reports from Nigeria [ 37 , 46 ] and Iraq [ 39 ]. However, this result is higher than the reports obtained from Nigeria [ 52 ], Egypt [ 50 ], and Poland [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean serum levels of AST, ALT and ALP in the current study were 47.07 (± 14.79), 35.83 (± 13.78) and 63.34 (±14.74) respectively; the result concur with reports from Nigeria [ 37 , 46 ] and Iraq [ 39 ]. However, this result is higher than the reports obtained from Nigeria [ 52 ], Egypt [ 50 ], and Poland [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…When the liver is compromised, liver enzymes leak enzymes into the circulating system causing increased activity. However, opposing result was obtained regarding the level of ALP, from previous studies from Nigeria, Iraq, France, and America [ 43 , 46 , 47 ] reported that HC use significantly reduced the level of ALP. This can also be explained by the fact that ALP derived mainly from liver and bone with approximately equal properties and the total effect of estrogen on bone.…”
Section: Discussionmentioning
confidence: 96%